Coronary Artery Disease and Health Literacy Via Public Health View - Yılmazel, Gülay; Ahçıoğlu, Asuman (Turkey Health Literacy Journal, 2021)
Coronary artery disease remains the leading major cause of death globally over the past 15 years. The disease is a pathological process characterized by atherosclerotic plaque deposition in the epicardial arteries. This process can be changed by lifestyle changes, early diagnosis and pharmacological treatments at preventive health care level. Health literacy acts as a mediator in the prevention and management of coronary artery disease. Individuals diagnosed with the disease should stay away from risk factors of the disease and comply with treatment regimens. Health literacy in these individuals includes the ability to understand drug directions, discharge and appointment forms, and education almaterials, as well as the ability to consider complex health systems. One in ten coronary artery patients suffers from limited health literacy. In order to change behavioral risk factors in coronary artery disease, which is an important public health problem of ourage, it will be beneficial to screen risky groups at first and to improve community  based coronary artery health literacy. Increasing studies to reveal the relationship between coronary artery disease and health literacy may open a new window to preventive health services. This study emphasizes the importance of coronary artery disease in preventive healthcare services and its relationship with health literacy.
Keywords: Coronary Artery Disease; Health Literacy; Preventive Health; Public Health; Service